2010
DOI: 10.1163/016942410x508253
|View full text |Cite
|
Sign up to set email alerts
|

Odd–Even Effects in the Friction of Self-Assembled Monolayers of Phenyl-Terminated Alkanethiols in Contacts of Different Adhesion Strengths

Abstract: We have studied the frictional properties of self-assembled monolayers (SAMs) of phenyl-terminated alkanethiols, C 6 H 5 (CH 2 ) n SH (n = 13-16) on template-stripped gold. The friction force was measured with atomic force microscopy (AFM), and the magnitude of the adhesion was controlled by immersing the sliding contact in ethanol (giving low adhesion) or dry N 2 gas (giving enhanced adhesion relative to ethanol). We observed a linear friction force as a function of load (F = μL) in the systems with low adhes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 66 publications
0
31
0
Order By: Relevance
“…As it can be seen for most cases the shear stress is higher for SAM-SAM contacts in comparison to a SAM-Au contact of the same alkanethiol system and at the same shear rate and normal pressure. Yang et al 36 27 have also reported weak dependence of friction on shear rate only at lower pressures of 200 MPa and almost no dependence at higher normal loads of 2 GPa. We note in our simulations, for the same alkanethiols system, the film thickness for a SAM-SAM system is roughly double that of a SAM-Au contact.…”
Section: Sam-sam Vs Sam-au Contactsmentioning
confidence: 96%
See 1 more Smart Citation
“…As it can be seen for most cases the shear stress is higher for SAM-SAM contacts in comparison to a SAM-Au contact of the same alkanethiol system and at the same shear rate and normal pressure. Yang et al 36 27 have also reported weak dependence of friction on shear rate only at lower pressures of 200 MPa and almost no dependence at higher normal loads of 2 GPa. We note in our simulations, for the same alkanethiols system, the film thickness for a SAM-SAM system is roughly double that of a SAM-Au contact.…”
Section: Sam-sam Vs Sam-au Contactsmentioning
confidence: 96%
“…Such odd-even effects on wetting 34 and tribological 35 properties of alkanethiol self assembled monolayers on gold are observed by experimental studies. 34,35 AFM measurements by Yang et al 36 have also shown oddeven effects for phenyl terminated monolayers, with higher values of friction coefficient for monolayers with odd number of methyl groups. It is suggested that this is due to more upright orientation angle of the end group (phenyl) with respect to the opposing surface.…”
Section: Introductionmentioning
confidence: 92%
“…It is further believed that the tribological behavior of more complex, multi-asperity interfaces can be predicted from models based on understanding of the behavior of individual asperities [8]. Many studies observed a linear relationship between the friction force (F F ) and the applied load (F N ) [36][37][38][39][40][41][42][43]. Such data are typically described by the Amontons' law:…”
Section: Nanotribology Of Monolayersmentioning
confidence: 99%
“…Wong et al studied the frictional properties of n-alkanethiols with 12 to 16 methylene units using FFM, and found that SAMs with an even number of methylene units consistently yielded higher friction than those with an odd number of methylene units [42]. Yang et al observed that for phenyl-terminated alkanethiol SAMs containing 13-16 methylene units, the coefficient of friction was systematically higher for the chains with odd methylene units [43]. In both cases, the monolayers with the terminal groups tilted farther from the surface normal exhibited lower friction.…”
Section: Influence Of Spacer Chain Lengthmentioning
confidence: 99%
“…[10][11][12][13][14] Self-assembled monolayers (SAMs) are formed at a solidliquid interface by molecules consisted of three units: a headgroup that binds to the substrate, a tailgroup that constitutes the outer surface of the film, and a backbone, usually a long chain, that connects the headgroup and the tailgroup. While pure alkylthiols are known to form SAMs that exhibit order on a large scale, [15][16][17][18] -conjugated thiols and their derivatives seem to be a better choice for applications in organic-and single-molecule electronics because of their intrinsic semiconducting properties. Relatively recently, Piotrowski et al 19 reported the synthesis and electronic properties of thioacetate-functionalized fullerene, Park et al 20 studied the formation of octylthioacetates SAMs on gold in the vapor phase.…”
Section: Introductionmentioning
confidence: 99%